PERAN KELOMPOK SADAR WISATA (POKDARWIS) PULAU TILAN DALAM PENGEMBANGAN DESA WISATA PULAU TILAN - Rindiani Nurfahima; Pawennari Hijjang (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
One of the tourism sectors with great potential to be developed is local wisdom-based tourism through tourism villages. The natural beauty and cultural richness of the Tilan Island Rantau Bais Tourism Village required the roles of competent community groups in the Tourism Village development, namely Tourism Awareness Group (Pokdarwis). The research objectives consisted of 1) explaining the tourism awareness group's roles in Tilan Island Tourism Village development in five dimensions, namely, the economic dimension, the social dimension, the cultural dimension, the environmental dimension, and the political dimension; and 2) explaining the supporting and inhibiting factors in realizing Tilan Island Tourism Village as a tourism destination. This research used a qualitative approach by collecting data through interviews, observation, and documentation. The research results indicated the tourism awareness group's roles of Tilan Island Tourism Village. The roles included developing business products to improve the community's economy and community empowerment, managing Tilan Island Tourism Village based on local wisdom as a tourist destination, and establishing collaboration with stakeholders. In its implementation, the supporting factors were the attractiveness and natural potential of Tilan Island, the spirit of the tourism awareness group management, and supports from the community, village government, and stakeholders. Meanwhile, the inhibiting factors included the limited funds available, pedestrian bridges, localization of community livestock, illegal crossings, lack of training related to tourism, and the community did not maintain cleanliness and existing facilities and infrastructure there. Moreover, the public interest in the tourism sector was low.